PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR IPA SISWA KELAS VII SMP TAMAN DEWASA IBU PAWIYATAN TAHUN AJARAN 2012/2013 - Jati Aurum; Hidayati Hidayati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
According to descriptive study, the research is intended to know the inclination of the result of IPA learning in class VII grade at SMP Taman Dewasa Ibu Pawiyatan by using jigsaw, Think Pair Share (TPS)and conventional model. According to comparative study is to know the difference of the result of IPA learning on the VII grade students by using the learning models. The research conducted in class VII grade of SMP Taman Dewasa Ibu Pawiyatan in Academic 2012/2013. The research population included all students of the VII grade of SMP Taman Dewasa Ibu Pawiyatanin academic 2012/2013 which consists of 4 classes with totaling 88 students. The samples were taken 3 classes by random sampling with class VII B and class VII C as experiment class and class VII D as control class. The collecting data by using documentation techniques to obtain the first skill of the students and using test technique to obtain data of the result of IPA learning. Validity of the questions were looked for by using product moment correlation. The question reliability was looked for using the KR-20 formula; the result is 0.72 rtt was explained was reliable. The data analysis techniques was calculated using the F or ANOVA test A, but previously conducted analysis of requirement test, including test distribution normality and homogenity of variance test.According to descriptive study, the result showed that the tendency of the result of IPA learning on class VII grade of SMP Taman Dewasa Ibu Pawiyatan in Academic 2012/2013 which using the model of cooperative learning (jigsaw  in very high categories, Think Pair Share (TPS), and conventional models ware high categories. In the F test using the dka = 2 and dbd = 52 obtained Fhitung = 7,07 whereas in table of The F values were 3.164 at significance level of 5 % and 4.98 at 1% significance level. Because the result of Fhitung  > F 1%, there were significant difference of the result of IPA learning on the class VII grade of SMP Taman Dewasa Ibu Pawiyatan in academic 2012/2013 between the learning presses using jigsaw  and Think Pair Share (TPS)cooperative learning models. From the result of Shceffe test described that jigsaw  was higher than Think Pair Share (TPS)cooperative leaning models, Think Pair Share (TPS)was higher than conventional cooperative learning models. The teacher must be increase quality of learning outcomes besides using jigsaw  and Think Pair Share (TPS)models to get maximal learning outcomes.